2015
DOI: 10.5539/gjhs.v7n5p288
|View full text |Cite
|
Sign up to set email alerts
|

Iranian Nurses' Views on Barriers and Facilitators in Patient Education: A Cross-Sectional Study

Abstract: Background:As a major factor in patient-centered care, patient education has a great impact on the quality of care provided by nurses; however, clinical nurses’ performance with regard to patient education is not satisfactory. This study is an attempt to investigate barriers and facilitators in patient education from nurses’ point of view.Methods:122 nurses at Jahrom University of Medical Sciences participated in this descriptive-cross sectional study. Sampling was based on the census method. The questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…[ 42 ] Participants in the present study believed that educational empowerment of the health-care team could play an important role in promoting patient education, which is consistent with other studies in which nurses believed that their inadequate knowledge and skills were the main obstacles to patient education. [ 40 43 ] Holding patient education workshops and developing patient education content for the health-care team were among the strategies proposed by the participants. In our study, the participants suggested that designating patient education and follow-up nurse is necessary to provide integrated and continuous education in the postkidney transplant period.…”
Section: Discussionmentioning
confidence: 99%
“…[ 42 ] Participants in the present study believed that educational empowerment of the health-care team could play an important role in promoting patient education, which is consistent with other studies in which nurses believed that their inadequate knowledge and skills were the main obstacles to patient education. [ 40 43 ] Holding patient education workshops and developing patient education content for the health-care team were among the strategies proposed by the participants. In our study, the participants suggested that designating patient education and follow-up nurse is necessary to provide integrated and continuous education in the postkidney transplant period.…”
Section: Discussionmentioning
confidence: 99%
“…Patient education, which starts at the admission of the patient to the hospital and continues until they are discharged, is a main element of patient-centred care. The intention is to provide the patient with information, skills, and attitudes regarding their disease, to increase quality of life, and help the patient become physically, psychologically, and socially selfsufficient as soon as possible (Aziznejad, Zabihi, Hossini, & Bighani, 2010;De Bruijn et al, 2007;De, Brandes, Krauth, & Petermann, 2008;Marcolongo et al, 2001;Potter & Perry, 1997;Ramezanli & Jahromi, 2015;Şenyuva & Taşocak, 2007;Wingard, 2005). The purpose of patient education, which is one of the main responsibilities of a nurse, is protection of the patient from complications related to their disease and other health problems that may accrue to their disease.…”
Section: Introductionmentioning
confidence: 99%
“…Patient education, which starts at the admission of the patient to the hospital and continues until they are discharged, is a main element of patient-centred care. It is one of the basic rights of the patient and their family/relatives (Nolan, Nolan, & Booth, 2001;Ramezanli & Jahromi, 2015;Stoop, van't Riet, & Berg, 2004). The purpose of patient education, which is one of the main responsibilities of a nurse, is protection of the patient from complications related to their disease and other health problems that may accrue to their disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Iran and other countries, some studies have investigated health education obstacles and have reported such factors as lack of manpower, budget and educational space (11), job dissatisfaction (1), cultural obstacles, fear and anxiety in expressing health behaviors, and lack of using new educational models and styles (12,13). These studies, however, have merely evaluated the barriers to education and a special domain in the opinion of a specific group and have disregarded the perspectives of the personnel of health care centers.…”
Section: Introductionmentioning
confidence: 99%